Coupling Charge‐Regulated Interfacial Chemistry to Electrokinetic Ion Transport in Bipolar SiO2‐Al2O3 Nanofluidic Diodes - Alexander Eden; Sumita Pennathur (Advanced Materials Interfaces)
Abstract Due to the surface‐dominant nature of electrokinetic ion transport in confined geometries, ionic currents in nanofluidic channels are fundamentally governed by the interfacial chemistry of the constituent substrates. In this work, the intrinsic coupling between charge‐regulated oxide surfaces and local changes in concentration and pH induced during the operation of bipolar nanofluidic diodes is numerically explored. Using a heterogeneous SiO2‐Al2O3 nanochannel as a representative example, field‐dependent ion accumulation and depletion effects are shown to have a marked effect on the local surface chemistry and resulting charge density of the amphoteric Al2O3 surface in particular. While the SiO2 surface tends to remain relatively indifferent to the presence of an applied potential due to its low point of zero charge (PZC), the comparatively high PZC of Al2O3 renders it much more susceptible to the extent of ion accumulation and depletion events which drive localized concentration and pH changes. Including this surface coupling in models can be necessary to capture the true behavior of real‐world devices; comparison with a fixed‐charge model demonstrates that only a fully coupled model can quantitatively reproduce reported experimental current measurements in heterogeneous SiO2‐Al2O3 nanochannels, the limiting behavior of which is revealed to stem from this surface‐to‐bulk coupling.